Laser-induced carbon-based magnetic phase graphite wave-absorbing material and preparation method thereof
Patent Information
- Application Number
- CN202610877604.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-17
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2046-06-17
AI Technical Summary
然而,现有的磁性碳复合材料制备方法存在以下共性缺陷:(1)需要采用多步工艺,如先通过水热、共沉淀等方法将金属离子负载于碳前驱体上,再在惰性气氛下进行长时间的高温热处理
[0023](1)本发明利用激光作为唯一能量源,在大气氛围下,于数秒至数分钟内同步完成木质素碳化、造孔和磁性相@石墨核壳结构的原位生长。基于预络合操作,本发明在诱导生物质前驱体碳化的同时,同步实现掺杂金属离子的原位还原与化合物转化,从而一步完成碳化与磁性组分原位负载的协同制备,有效避免传统多步法的诸多缺陷。本发明将传统上需要数小时、涉及多步化学反应和高温炉热解的复杂流程,简化为一个快速、绿色的单步过程,降低了能耗、缩短了制备周期,并避免了有毒化学试剂的使用,符合绿色可持续发展的理念。
Smart Images

Figure CN122403426B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of materials preparation and microwave absorbing materials, specifically relating to a laser-induced carbon-based magnetic phase@graphite microwave absorbing material and its preparation method. The magnetic porous carbon microwave absorbing material of this invention is constructed by pre-complexing and anchoring metal ions and synchronously constructing a magnetic phase@graphite core-shell structure in situ using laser. Background Technology
[0002] With the rapid development of modern electronic information technology, the importance of electromagnetic wave absorbing materials in solving electromagnetic pollution is becoming increasingly prominent. An ideal absorbing material must simultaneously meet the comprehensive performance requirements of "thin thickness, light weight, wide bandwidth, and strong absorption." Carbon materials have advantages such as light weight, large specific surface area, and tunable dielectric properties; however, pure carbon materials have a simple loss mechanism, poor impedance matching, and limited absorption performance.
[0003] Introducing magnetic components to construct carbon / magnetic composite materials is considered to introduce magnetic loss and optimize impedance matching. However, existing methods for preparing magnetic carbon composite materials have the following common defects: (1) They require multi-step processes, such as loading metal ions onto carbon precursors through hydrothermal or co-precipitation methods, followed by long-term high-temperature heat treatment in an inert atmosphere. These methods are cumbersome, time-consuming, and energy-intensive. (2) Metal salts tend to agglomerate during drying, resulting in uneven distribution and uncontrollable size of nanoparticles. (3) It is difficult to form a uniform and controllable graphite shell on the surface of magnetic particles in situ, making it difficult to enhance interfacial polarization loss using the core-shell structure, and limiting the magnetic-dielectric synergistic effect. Therefore, it is urgent to develop a new preparation method that is simple, green, efficient, and can precisely control the microstructure of magnetic composite materials. Summary of the Invention
[0004] The purpose of this invention is to overcome the shortcomings of existing magnetic composite technologies and provide a broadband, efficient, and environmentally friendly laser-induced magnetic porous carbon and a preparation method that can simultaneously achieve in-situ magnetic composite and carbonization. The material obtained by this invention exhibits outstanding microwave absorption performance, with a reflection loss (RL) of -41.4 dB at a thickness of 1.6 mm, and an effective absorption bandwidth covering the entire Ku-band. The material preparation process is simple, environmentally friendly, low-cost, and highly controllable in structure. Multi-scale control of the microwave absorption performance can be achieved by adjusting the mass ratio of lignin to a soluble magnetic metal source, the laser power, and the laser scanning rate.
[0005] The specific technical solution adopted in this invention is as follows:
[0006] In a first aspect, the present invention provides a method for preparing laser-induced carbon-based magnetic phase@graphite microwave absorbing material, as detailed below:
[0007] S1: Dissolve lignin and a soluble magnetic metal source in an aqueous solution to obtain a lignin-magnetic metal complex precursor solution;
[0008] S2: Add alkali to the lignin-magnetic metal complex precursor solution, then add film-forming aid and mix evenly to obtain a mixed solution. Dry the solution to obtain a lignin-magnetic metal complex composite film.
[0009] S3: The lignin-magnetic metal complex composite film is subjected to laser irradiation to obtain a carbonized magnetic composite film; the carbonized magnetic composite film is washed and vacuum dried to obtain a laser-induced carbon-based magnetic phase@graphite microwave absorbing material.
[0010] Preferably, in S1, the concentration of lignin in the lignin-magnetic metal complex precursor solution is 0.05 ~ 0.3 g / mL.
[0011] Preferably, in step S1, the soluble magnetic metal source is a soluble magnetic metal salt or its hydrate, wherein the soluble magnetic metal salt is one or more selected from ferric nitrate, nickel nitrate, ferric chloride, nickel chloride, ferric sulfate, and nickel sulfate; the mass ratio of lignin to the soluble magnetic metal source is 5~40:1. Preferably, the soluble magnetic metal source is ferric nitrate nonahydrate.
[0012] Preferably, in step S1, the dissolution process employs a water bath or oil bath heating treatment to ensure uniform heating of the solution. The heating temperature is 60℃ ~ 80℃, and the time is 2 h ~ 24 h. Preferably, a water bath heating is used, with a temperature of 80℃ and a time of 8 h.
[0013] Preferably, in step S2, the alkali is sodium hydroxide or potassium hydroxide, preferably solid sodium hydroxide, and the mass ratio of alkali to lignin is 0.2~0.4:1. This invention uses an alkali to provide OH... - It reacts with the phenolic hydroxyl groups in lignin to deprotonate the phenolic hydroxyl groups and then undergoes a neutralization reaction with the carboxyl groups.
[0014] Preferably, in step S2, the film-forming aid is polyethylene oxide, polyvinyl alcohol, polyvinylpyrrolidone, polylactic acid, or polybutylene succinate; in the mixed solution, the mass ratio of lignin to the film-forming aid is 0.5 to 2:1.
[0015] Preferably, the film-forming aid of the present invention is polyethylene oxide, which is added in the form of an aqueous solution, and the concentration of the polyethylene oxide aqueous solution is 0.005-0.03 g / mL. Preferably, the preparation method of the polyethylene oxide aqueous solution is as follows: [The text abruptly ends here, so the translation stops.] w = 400,000 polyoxyethylene was added to water and reacted at a heating temperature of 65°C and a stirring speed of 400 r / s for 4 h.
[0016] Preferably, in step S2, the drying temperature is 25~40℃.
[0017] Preferably, in step S3, the laser used for laser irradiation has a wavelength range of 400-600nm, a laser power of 1.2-3 W, and a laser scanning rate of 2-8 mm / s.
[0018] When polyethylene oxide (PEO) is selected as the film-forming aid, a blue laser is preferred. Since PEO lacks conjugated structures or chromophores that absorb energy in the visible light region (400-700 nm), the PEO in the lignin / PEO film does not degrade under laser irradiation in this invention. Preferably, a 450 nm wavelength laser source is used to achieve efficient conversion of photon energy into heat energy, which can irradiate lignin. This method is low-cost and has high energy utilization. More preferably, the laser power is 2.4 W and the laser scanning rate is 8 mm / s. Under these conditions, the laser-induced magnetic porous carbon material prepared has the optimal reflection loss value.
[0019] Preferably, in step S3, each carbonized magnetic composite membrane is washed with water and then vacuum filtered, and the pore size of the microporous filter membrane used during filtration is 0.22 μm.
[0020] Preferably, in step S3, the vacuum degree during vacuum drying is -0.9 bar, the drying temperature is 80-90℃, and the drying time is 10-15 h.
[0021] In a second aspect, the present invention provides a laser-induced carbon-based magnetic phase@graphite microwave absorbing material obtained by the preparation method described in any one of the first aspects.
[0022] Compared with the prior art, the present invention has the following advantages:
[0023] (1) This invention utilizes laser as the sole energy source to simultaneously complete lignin carbonization, pore formation, and in-situ growth of the magnetic phase@graphite core-shell structure within seconds to minutes under atmospheric conditions. Based on the pre-complexation operation, this invention simultaneously achieves in-situ reduction and compound transformation of doped metal ions while inducing the carbonization of biomass precursors, thereby completing the synergistic preparation of carbonization and in-situ loading of magnetic components in one step, effectively avoiding many defects of traditional multi-step methods. This invention simplifies the complex process that traditionally requires several hours and involves multiple chemical reactions and high-temperature furnace pyrolysis into a rapid and green single-step process, reducing energy consumption, shortening the preparation cycle, and avoiding the use of toxic chemical reagents, which is in line with the concept of green and sustainable development.
[0024] (2) Lignin, as the second largest natural polymer in nature and a major byproduct of the papermaking industry, has a high carbon content and low cost, making it an ideal green precursor for laser in-situ magnetic carbonization research. This invention utilizes the pre-complexation and anchoring effect of the abundant functional groups on lignin molecules on magnetic metal ions to ensure that magnetic metal elements are pre-complexed and uniformly dispersed at the molecular level. During the subsequent laser irradiation process, the anchored magnetic metal is transformed in situ into magnetic phase@graphite core-shell nanoparticles, effectively avoiding many defects common in traditional non-complexing methods (lignin and magnetic metal source are mixed and dissolved at room temperature): a) Metal ions only adhere to the lignin surface by electrostatic adsorption or weak interaction, making it difficult to penetrate into the interior and fully coordinate with functional groups; b) Due to the lack of sufficient thermal energy to drive the diffusion of metal ions into the interior of lignin, the metal salts are prone to agglomerate into micron-sized large particles during the subsequent carbonization process; c) Simple mixing at room temperature may induce a runaway thermal reaction, leading to local overheating and uneven distribution of metal ions in the lignin matrix, ultimately resulting in severe agglomeration, inconsistent size, poor dispersion, and deterioration of microwave absorption performance of the magnetic nanoparticles formed during subsequent laser carbonization.
[0025] Furthermore, by changing the laser power during the laser irradiation process, this invention can continuously and precisely control the phase composition of the magnetic core (e.g., from iron oxide to Fe3C), the thickness of the graphite shell, and the defect density of the carbon matrix, providing a green new solution for the controllable preparation of magnetic composite materials.
[0026] (3) The microwave absorption performance of pure carbon materials mainly depends on the dielectric loss of the carbon matrix itself (such as dipole polarization and defect-induced polarization relaxation). The loss mechanism is simple and limited by the high real part of the dielectric constant of carbon materials. It often requires a large matching thickness to meet the impedance matching condition. It is also difficult to achieve the best impedance matching by relying solely on dielectric loss, resulting in a narrow effective absorption bandwidth. The magnetic phase@graphite core-shell structure constructed in this invention, on the one hand, provides magnetic loss pathways such as natural resonance and exchange resonance, which enhances the magnetic response capability of electromagnetic waves; on the other hand, the large number of interfaces formed between the graphite shell and the magnetic core can induce significant interface polarization effects, and the shell itself can also serve as a dielectric loss medium. This dielectric-magnetic synergy achieves a balance between excellent impedance matching and high attenuation capability, allowing more electromagnetic waves to enter the interior of the absorber and be dissipated rather than reflected at the surface, thereby achieving stronger absorption and a wider effective bandwidth with a thinner thickness. Furthermore, the performance adjustment of pure carbon materials has a low degree of freedom, and the dielectric properties can usually only be adjusted by changing the carbonization temperature or the pore-forming strategy. However, this invention can achieve multi-dimensional and continuously adjustable performance optimization by independently controlling multiple parameters such as the type (Fe, Ni or alloy) and content of the magnetic phase, the thickness of the graphite shell and the degree of graphitization.
[0027] (4) This invention achieves integrated control of metal ion pre-anchoring at the molecular level, in-situ carbonization and reduction, and graphite shell growth. The prepared magnetic lignin-derived porous carbon material has a unique multi-level structure that brings about a synergistic effect of multiple electromagnetic loss mechanisms. First, the porous carbon framework promotes multiple scattering of electromagnetic waves and interfacial polarization. Second, the uniformly dispersed magnetic phase@graphite core-shell nanoparticles not only provide effective magnetic loss, but the rich heterogeneous interface formed between them and the carbon matrix significantly enhances the interfacial polarization loss. This synergistic effect of dielectric-magnetic loss, combined with optimized impedance matching, enables the material to achieve strong absorption of high-frequency electromagnetic waves (Ku band) (RL = -41.4dB) with a thickness of only 1.6 mm, meeting the requirements of "thin, light, wide, and strong" for microwave absorbing materials, and has broad application prospects in electromagnetic shielding and stealth coatings. Attached Figure Description
[0028] Figure 1 XPS spectra of lignin and the laser-induced carbon-based magnetic phase@graphite absorbing material in Example 1;
[0029] Figure 2 SEM images of laser-induced carbon-based magnetic phase@graphite microwave absorbing materials in lignin (left) and Example 1 (right);
[0030] Figure 3 Raman spectra of lignin and the laser-induced carbon-based magnetic phase@graphite absorbing material prepared in Example 12;
[0031] Figure 4 XRD patterns of lignin and laser-induced carbon-based magnetic phase@graphite microwave absorbing materials prepared in Examples 1 and 2;
[0032] Figure 5 HRTEM images of lignin, laser-induced magnetic porous carbon absorbing materials prepared in Examples 1 and 2, and carbon-based magnetic phase@graphite absorbing materials;
[0033] Figure 6 The hysteresis loops of the laser-induced carbon-based magnetic phase@graphite absorbing materials prepared in Examples 1, 2, 3 and 4;
[0034] Figure 7 The reflection loss curves of the laser-induced carbon-based magnetic phase@graphite absorbing material at different thicknesses in Example 1 are shown.
[0035] Figure 8 Reflection loss curves (thickness = 1.6 mm) of laser-induced carbon-based magnetic phase@graphite absorbing materials prepared in Examples 1, 2, 3 and 4. Detailed Implementation
[0036] The present invention will be further described and illustrated below with reference to the accompanying drawings and specific embodiments. The technical features of each embodiment of the present invention can be combined accordingly, provided that there is no mutual conflict.
[0037] The following examples provide those skilled in the art with guidance on how to manufacture and evaluate the invention. These examples are merely illustrative of the present disclosure and do not limit its scope. While every effort has been made to ensure accuracy regarding numerical values (e.g., quantities, temperatures, etc.), some errors and deviations should be considered. Unless otherwise stated, temperatures are in °C or at ambient temperature, and pressures are at or near atmospheric pressure.
[0038] Unless otherwise specified, all reagents and raw materials used in this invention are commercially available.
[0039] The embodiments of this invention specifically employ the following typical, but not limited, preparation process to implement the laser-induced carbon-based magnetic phase@graphite microwave absorbing material preparation method described in the invention content:
[0040] S1: First, prepare a lignin aqueous solution with a mass-to-volume ratio of lignin to deionized water of 0.5~3 g : 10 mL. Then, add a soluble magnetic metal source (ferric nitrate, nickel nitrate, ferric chloride, nickel chloride, ferric sulfate, nickel sulfate, or hydrates of these salts) to the lignin aqueous solution with a mass ratio of 5~40:1. Heat in a water bath at 60~80℃ for 2~24 h to obtain a lignin-magnetic metal complex precursor solution.
[0041] S2: Sodium hydroxide solid was dissolved in a lignin-magnetic metal complex precursor solution at a mass ratio of sodium hydroxide to lignin of 1:5. Subsequently, a film-forming aid (ethylene oxide, polyvinyl alcohol, polyvinylpyrrolidone, polylactic acid, or polybutylene succinate) was added to water and heated with stirring to obtain a film-forming aid solution with a concentration of 0.0004~0.03 g / mL. A film-forming aid aqueous solution was added to the lignin-magnetic metal complex precursor solution at a mass ratio of lignin to polyethylene oxide of 4:3 and mixed uniformly to obtain a mixed solution. This mixed solution was poured into a petri dish and then dried at a low temperature of 25~40℃ to obtain a lignin-magnetic metal complex composite film.
[0042] S3: The lignin-magnetic metal complex composite film was irradiated with a laser (laser wavelength 400-600 nm, laser power 1.2-3 W, laser scanning rate 2-8 mm / s) to obtain a carbonized magnetic composite film. The obtained carbonized lignin film was washed with deionized water, vacuum filtered using a microporous membrane with a pore size of 0.22 μm, and finally the filtered product was vacuum dried to obtain a laser-induced carbon-based magnetic phase@graphite microwave absorbing material.
[0043] The method of this invention utilizes laser-induced carbonization to induce in-situ formation of magnetic nanoparticles, which offers significant advantages over the traditional two-step chemical impregnation-furnace pyrolysis method. In conventional methods, biomass precursors require prolonged immersion in metal salt solutions, resulting in uneven distribution and agglomeration after drying. Subsequently, carbonization in a high-temperature furnace at 500-1000°C for several hours is necessary, leading to extremely high energy consumption. The laser process of this invention integrates the traditional two-step method into a one-step ultrafast process, which can simultaneously complete carbonization and magnetic doping in just a few seconds to a few minutes, and has the following advantages: (1) Rapid and localized heating can achieve dynamic control of phase transformation, thereby producing a metastable phase combination structure that is difficult to obtain under slow furnace heating conditions; (2) Lignin itself is both a carbon source and a reducing agent, which promotes the in-situ formation of core-shell structure; (3) The laser-induced instantaneous nucleation and growth process makes the nanoparticles uniformly dispersed, and the material exhibits clear magnetic resonance and strong interfacial polarization; (4) The iron nanoparticles formed in situ catalyze the graphitization of the surrounding carbon, and a perfect graphite layer can be formed with less energy input than that required for the carbonization of pure lignin; (5) The process is green, environmentally friendly and sustainable, requires no pretreatment, does not produce chemical waste liquid, and the localized heating characteristics reduce energy consumption, shortening the processing time from several hours to several minutes.
[0044] The following examples will illustrate the method of the present invention and the performance effects of the obtained materials.
[0045] Example 1
[0046] This embodiment prepares a laser-induced carbon-based magnetic phase@graphite microwave absorbing material. The specific implementation steps are as follows:
[0047] S1: First, dissolve 1 g of lignin powder in 10 mL of deionized water to obtain a lignin aqueous solution. Then add 0.05 g of ferric nitrate nonahydrate solid, stir to dissolve, mix evenly, and heat in a water bath at 80°C for 8 h to obtain a lignin-iron complex precursor solution.
[0048] S2: 0.2 g of solid sodium hydroxide was dissolved in the lignin-iron complex precursor solution. Then, 0.75 g of polyethylene oxide was added to 40 mL of deionized water, heated to 65°C, and stirred at 400 r / s for 4 h to obtain a polyethylene oxide solution with a concentration of 0.01875 g / mL. Following a lignin to polyethylene oxide mass ratio of 4:3, an aqueous polyethylene oxide solution was added to the lignin-iron complex precursor solution containing dissolved sodium hydroxide and mixed uniformly to obtain a lignin-iron complex polyethylene oxide mixed solution. 50 mL of this mixed solution was poured into a 100 mm petri dish and then dried at 40°C for 36 h to obtain the lignin-iron complex composite membrane.
[0049] S3: The lignin-iron complex composite film was irradiated with a blue laser with a wavelength of 450 nm, a laser power of 3 W, and a maximum laser scanning rate of 10 mm / s to obtain a carbonized magnetic composite film. The laser power used for irradiation was 80% of the upper limit of the blue laser power, i.e., 2.4 W, and the laser scanning rate was 80% of its upper limit, i.e., 8 mm / s. The obtained carbonized lignin film was washed with 30 mL of deionized water, vacuum filtered using a microporous membrane with a pore size of 0.22 μm, and finally vacuum dried. That is, vacuum drying at a vacuum degree of -0.9 bar and 80 °C for 12 h yielded a laser-induced carbon-based magnetic phase@graphite absorbing material.
[0050] The laser-induced carbon-based magnetic phase@graphite microwave absorbing material (absorbent) of this embodiment was uniformly mixed with paraffin at a mass ratio of 3:7 (i.e., absorbent content of 30 wt%), and pressed into a standard coaxial ring sample (inner diameter 3.0 mm, outer diameter 7.04 mm, thickness 2.0 mm) in a mold. The electromagnetic parameters of the sample in the range of 2 ~ 18 GHz were tested using a vector network analyzer (ROHDE & SCHWARZ ZNB 40).
[0051] like Figure 1 The figure shows the XPS spectra of the laser-induced magnetic porous carbon material and lignin. As can be seen from the figure, the absorbing material is mainly composed of C and O elements, and also exhibits an Fe 2p peak, while lignin is mainly composed of C, O, and Na elements. This indicates that the laser-induced technology successfully achieved the carbonization and in-situ magnetic recombination of lignin.
[0052] like Figure 2 The image shows SEM images of lignin and the prepared laser-induced carbon-based magnetic phase@graphite microwave absorbing material. The images show that lignin has a non-porous structure, while the microwave absorbing material has a hierarchical porous structure, indicating that laser irradiation technology successfully constructed the porous structure.
[0053] like Figure 3 The figure shows the Raman spectra of lignin and the prepared laser-induced carbon-based magnetic phase@graphite absorbing material. As can be seen from the figure, no obvious characteristic peaks were observed in the Raman spectrum of lignin, which is mainly attributed to the strong laser-induced fluorescence induced by the abundant aromatic conjugated structures in the lignin molecule. After laser irradiation, Example 1 showed fluorescence at approximately 1350 cm⁻¹. -1 Approximately 1580 cm -1 Two partially overlapping broad peaks appear at the point, corresponding to the D band (defects and disordered structure) and G band (sp) of carbon materials, respectively. 2The presence of the G band (characteristic peaks of graphite in hybrid carbon) indicates the formation of graphitized carbon in the sample. Simultaneously, at approximately 2800 cm⁻¹... -1 The appearance of broadened 2D bands indicates the formation of stacked graphitic carbon structures.
[0054] like Figure 7 The figure shows the reflection loss curves of the laser-induced carbon-based magnetic phase@graphite absorbing material under different thickness conditions. As can be seen from the figure, this absorbing material exhibits excellent electromagnetic wave absorption performance, with a reflection loss of -41.4 dB at a thickness of only 1.6 mm. The maximum effective absorption bandwidth is 5.94 GHz, covering the entire Ku-band.
[0055] Example 2
[0056] This embodiment uses the same preparation method as Example 1, but differs from Example 1 in that: in step S3, the laser irradiation power is 100% of the upper limit of the blue laser power, and the rest is the same as Example 1.
[0057] The laser-induced carbon-based magnetic phase@graphite absorbing material from Example 2 was uniformly mixed with paraffin at a mass ratio of 3:7 (i.e., absorber content of 30 wt%), and then pressed into standard coaxial ring samples (inner diameter 3.0 mm, outer diameter 7.04 mm, thickness 2.0 mm) in a mold. The electromagnetic parameters of the samples in the range of 2–18 GHz were measured using a vector network analyzer (ROHDE & SCHWARZ ZNB 40).
[0058] The results showed that although the absorbing material prepared in this embodiment was within the effective performance range, compared with Example 1, the laser irradiation power was increased. In the sample obtained in this embodiment, the shell thickness in the magnetic phase@graphite core-shell structure was increased. When the thickness of the absorbing material was 5.5 mm, the reflection loss value was the minimum of -16.52 dB. The maximum effective absorption bandwidth was 6.36 GHz.
[0059] like Figure 4The image shows the XRD patterns of lignin and the laser-induced carbon-based magnetic phase@graphite microwave absorbing materials prepared in Examples 1 and 2. The broad peaks appearing in the range of 2θ ≈ 7-17° correspond to the small amount of cellulose and its amorphous characteristics remaining during the lignin extraction process. In Examples 1 and 2, a broad diffraction peak centered at 2θ = 21.6° appears, indicating the formation of amorphous carbon. Simultaneously, diffraction peaks belonging to Fe3C and Fe3O4 appear in both examples, confirming the successful introduction of magnetic nanoparticles. Compared to Example 1, the XRD pattern of Example 2 shows more and more obvious diffraction impurities, indicating that the composition of the magnetic phase becomes more complex with increasing laser power. This may be due to higher power promoting the formation of multiple phases such as Fe3C and Fe3O4 or a redistribution of phase proportions. These results demonstrate that the phase types and relative contents of magnetic nanoparticles can be effectively controlled by adjusting the laser power.
[0060] like Figure 5 The image shows HRTEM images of lignin and the laser-induced carbon-based magnetic phase@graphite absorbing materials prepared in Examples 1 and 2. The lignin raw material exhibits an amorphous carbon structure without core-shell particles. In contrast, Examples 1 and 2, after pre-complexation and laser irradiation, both produced core-shell structures where nanoparticles were tightly wrapped by clear lattice fringes. Combined with the aforementioned XRD and Raman spectroscopy analyses, these lattice fringes correspond to a graphite carbon layer, and the wrapped nanoparticles are a magnetic phase (such as Fe3C), indicating the formation of a magnetic phase@graphite core-shell structure. Comparing Examples 1 and 2, it is evident that the graphite shell thickness significantly increases with increasing laser power. This indicates that the shell thickness of the core-shell structure can be effectively controlled by adjusting the laser power.
[0061] Example 3
[0062] This embodiment uses the same preparation method as Example 1, but differs from Example 1 in that: in step S1, the mass ratio of lignin to ferric nitrate nonahydrate is 30:1; in step S3, the laser irradiation power is 60% of the upper limit of the blue laser power, and the rest is the same as Example 1.
[0063] The laser-induced carbon-based magnetic phase@graphite absorbing material from Example 3 was uniformly mixed with paraffin at a mass ratio of 3:7 and pressed into a standard coaxial ring sample (inner diameter 3.0 mm, outer diameter 7.04 mm, thickness 2.0 mm) in a mold. The electromagnetic parameters of the sample in the range of 2 to 18 GHz were tested using a vector network analyzer (ROHDE & SCHWARZ ZNB 40).
[0064] The results showed that although the absorbing material prepared in this embodiment was within the effective performance range, the magnetic precursor concentration was lower than that in Example 1. The magnetic phase density was reduced in the sample obtained in this embodiment, and the minimum reflection loss was -26.1 dB when the thickness was 5.8 mm. The maximum effective absorption bandwidth was 2.52 GHz.
[0065] Example 4
[0066] This embodiment uses the same preparation method as Example 1, but differs from Example 1 in that: in step S3, the laser irradiation power is 40% of the upper limit of the blue laser power, the laser scanning rate is 40% of the upper limit of its scanning rate, and the rest is the same as Example 1.
[0067] The laser-induced carbon-based magnetic phase@graphite absorbing material from Example 4 was uniformly mixed with paraffin at a mass ratio of 3:7 and pressed into standard coaxial ring samples (inner diameter 3.0 mm, outer diameter 7.04 mm, thickness 2.0 mm) in a mold. The electromagnetic parameters of the samples in the range of 2–18 GHz were measured using a vector network analyzer (ROHDE & SCHWARZ ZNB 40).
[0068] The results showed that although the absorbing material prepared in this embodiment was within the effective performance range, compared with Example 1, the laser irradiation power was reduced and the scanning rate was slowed down. In the sample obtained in this embodiment, the reflection loss value was the lowest at a thickness of 2.3 mm, which was -24.2 dB. The maximum effective absorption bandwidth was 5.64 GHz.
[0069] Example 5 (Comparative Example 1)
[0070] This embodiment uses the same preparation method as Example 1, but differs from Example 1 in that: in step S1, the mass ratio of lignin to ferric nitrate nonahydrate is 25:18, and the rest is the same as in Example 1, as follows: S1: First, 1 g of lignin powder is dissolved in 10 mL of deionized water to obtain a lignin aqueous solution, and then 0.72 g of ferric nitrate nonahydrate solid is added, stirred and dissolved, and after uniform mixing, it is heated in a water bath at 80°C for 8 h to obtain a lignin-iron complex precursor solution.
[0071] S2: 0.2 g of solid sodium hydroxide was dissolved in the lignin-iron complex precursor solution. Then, 0.75 g of polyethylene oxide was added to 40 mL of deionized water, heated to 65°C, and stirred at 400 r / s for 4 h to obtain a polyethylene oxide solution with a concentration of 0.01875 g / mL. Following a lignin to polyethylene oxide mass ratio of 4:3, an aqueous polyethylene oxide solution was added to the lignin-iron complex precursor solution containing dissolved sodium hydroxide and mixed uniformly to obtain a lignin-iron complex polyethylene oxide mixed solution. 50 mL of this mixed solution was poured into a 100 mm petri dish and then dried at 40°C for 36 h to obtain the lignin-iron complex composite membrane.
[0072] S3: The lignin-iron complex composite film was irradiated with a blue laser with a wavelength of 450 nm, a laser power of 3 W, and a maximum laser scanning rate of 10 mm / s to obtain a carbonized magnetic composite film. The laser power used for irradiation was 80% of the upper limit of the blue laser power, and the laser scanning rate was 80% of its upper limit. The obtained carbonized lignin film was washed with 30 mL of deionized water, vacuum filtered using a microporous membrane with a pore size of 0.22 μm, and finally the filtered product was vacuum dried. That is, vacuum drying at a vacuum degree of -0.9 bar and 80 °C for 12 h yielded a laser-induced carbon-based magnetic phase@graphite microwave absorbing material.
[0073] The laser-induced carbon-based magnetic phase@graphite absorbing material of the above embodiments was uniformly mixed with paraffin at a mass ratio of 3:7, and pressed into standard coaxial ring samples (inner diameter 3.0 mm, outer diameter 7.04 mm, thickness 2.0 mm) in a mold. The electromagnetic parameters of the samples in the range of 2 to 18 GHz were tested using a vector network analyzer (ROHDE & SCHWARZ ZNB 40).
[0074] The results showed that the absorbing material prepared in this embodiment was not within the effective performance range. Compared with Example 1, the magnetic precursor concentration was increased. In the sample obtained in this embodiment, the magnetic phase density increased. When the thickness was 5.5 mm, the minimum reflection loss value was -8.6 dB. There was no effective absorption band with reflection loss below -10 dB.
[0075] like Figure 6The figure shows the hysteresis loops of the laser-induced carbon-based magnetic phase@graphite absorbing materials prepared in Examples 1, 2, 3, 4, and 5. It can be seen that by changing the magnetic precursor concentration, laser power, and laser scanning rate, the saturation magnetization and coercivity of the magnetic lignin-derived porous carbon composite material were successfully controlled. This change in magnetic properties is attributed to and effectively reflects the change in the magnetic phase within the material. Example 5 had the largest amount of magnetic phase added and the highest saturation magnetization, but its absorption performance was inferior to that of Examples 1-4. This is because excessive magnetic phase easily leads to aggregation, causing the natural resonance peak to shift out of the target frequency band and impedance matching to deteriorate, thus weakening loss capability and enhancing electromagnetic wave reflection.
[0076] The wave absorption performance of the materials prepared in Examples 1, 2, 3, 4, and 5 was investigated by comparing and analyzing their reflection loss curves. The results are as follows: Figure 8 As shown, compared with Examples 2, 3, 4 and 5, the material prepared in Example 1 has the best reflection loss value, achieving a reflection loss of -41.4 with a thickness of only 1.6 mm. This indicates that the control of magnetic precursor concentration, laser power and laser scanning rate is of great significance for optimizing the dielectric-magnetic synergistic loss effect and microwave absorption performance of the material.
[0077] Therefore, the laser-induced carbon-based magnetic phase@graphite microwave absorbing material of this invention can simultaneously complete the composite of the magnetic phase, the construction of the core-shell structure, and the formation of a porous carbon framework through a single-step laser processing, making the process simple and efficient. The resulting material exhibits high reflection loss and broadband absorption characteristics; the magnetic phase, shell, and pore structure can be flexibly controlled; and the raw material is an industrial lignin byproduct, making it environmentally friendly and low-cost. Furthermore, this invention achieves high-value conversion of waste materials, meeting practical application needs and showing excellent application prospects in the field of microwave absorbing materials technology.
[0078] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the invention. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the invention. Therefore, all technical solutions obtained through equivalent substitution or transformation fall within the protection scope of the present invention.
Claims
1. A method for preparing laser-induced carbon-based magnetic phase@graphite microwave absorbing material, characterized in that, include: S1: A lignin-magnetic metal complex precursor solution is obtained by pre-complexing lignin with a soluble magnetic metal source in an aqueous solution. The pre-complexing reaction is carried out by water bath or oil bath heating treatment at a temperature of 60℃~80℃ for 2 h~24 h. During this process, the phenolic hydroxyl and carboxyl groups on the lignin form coordinate bonds with the metal ions to achieve uniform anchoring of the metal ions. The mass ratio of lignin to soluble magnetic metal source is 5~40:
1. S2: Add alkali to the lignin-magnetic metal complex precursor solution, then add film-forming aid and mix evenly to obtain a mixed solution. Dry the solution to obtain a lignin-magnetic metal complex composite film. S3: The lignin-magnetic metal complex composite film is subjected to laser irradiation to obtain a carbonized magnetic composite film; the laser power of the laser irradiation is 1.2~3 W, and the laser scanning rate is 2~8 mm / s; during the laser irradiation process, lignin is carbonized to form a porous carbon skeleton, and the anchored magnetic metal ions are transformed in situ to form magnetic nanoparticles, and a graphite shell layer is grown in situ on the surface of the magnetic nanoparticles to form a magnetic phase@graphite core-shell structure; the carbonized magnetic composite film is washed and vacuum dried to obtain a laser-induced carbon-based magnetic phase@graphite microwave absorbing material.
2. The method for preparing a laser-induced carbon-based magnetic phase@graphite microwave absorbing material according to claim 1, characterized in that, In S1, the concentration of lignin in the lignin-magnetic metal complex precursor solution is 0.05 ~ 0.3 g / mL.
3. The method for preparing a laser-induced carbon-based magnetic phase@graphite microwave absorbing material according to claim 1, characterized in that, In step S1, the soluble magnetic metal source is a soluble magnetic metal salt or its hydrate, and the soluble magnetic metal salt is one or more of ferric nitrate, nickel nitrate, ferric chloride, nickel chloride, ferric sulfate, and nickel sulfate.
4. The method for preparing a laser-induced carbon-based magnetic phase@graphite microwave absorbing material according to claim 1, characterized in that, In S2, the alkali is sodium hydroxide and potassium hydroxide, and the mass ratio of alkali to lignin in the mixed solution is 0.2~0.4:
1.
5. The method for preparing a laser-induced carbon-based magnetic phase@graphite microwave absorbing material according to claim 1, characterized in that, In S2, the film-forming aid is polyethylene oxide, polyvinyl alcohol, polyvinylpyrrolidone, polylactic acid, or polybutylene succinate; in the mixed solution, the mass ratio of lignin to film-forming aid is 0.5~2:
1.
6. The method for preparing a laser-induced carbon-based magnetic phase@graphite microwave absorbing material according to claim 1, characterized in that, In step S2, the drying temperature is 25~40℃.
7. The method for preparing a laser-induced carbon-based magnetic phase@graphite microwave absorbing material according to claim 1, characterized in that, In S3, the laser wavelength used for laser irradiation is selected from 400-600nm. During the laser irradiation process, magnetic metal ions are reduced in situ by the reducing gas or carbon matrix generated during the carbonization of lignin, and the surrounding amorphous carbon is catalyzed to be converted into a graphite layer, forming a core-shell structure in which magnetic nanoparticles are coated with a graphite layer.
8. The method for preparing a laser-induced carbon-based magnetic phase@graphite microwave absorbing material according to claim 1, characterized in that, In S3, the vacuum degree during vacuum drying is -0.9 bar, the drying temperature is 80-90℃, and the time is 10-15 h.
9. A laser-induced carbon-based magnetic phase@graphite microwave absorbing material obtained by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
Aerogel composite material and preparation method thereof
CN115925426A
Biomass carbon composite wave-absorbing material and preparation method thereof
CN120329913A
